The effect of intimate partner violence on unintended pregnancies a Philippine case - Bongco, Emmanuel S. (School of Economics, University of the Philippines Diliman, 2018)
We associate intimate partner violence to unintended pregnancies because intimate partner violence is considered a risk factor to a number of fertility and reproductive_related problems. We focus the study in the Philippine setting, because of the lack of studies between the relationship of violence against women and unintended pregnancies in developing countries. Provided with the National Demographic and Health Survey data for 2017 in the Philippines, we used OLS, probit, logit, logistic, and biprobit regressions to study and prove the relationship between IPV and unintended pregnancy, we also explored the effects of sociodemographic factors, abuse_related factors such as severity of the violence and number of control issues, factors related to women_s autonomy, and the partner_s characteristics. The odds of women to experience an unintended pregnancy were elevated when they experienced any form of violence (OR, 1.409). This observation was significant at 5 percent significance level. The findings of this study can better promote action by public and private institutions against violence against women, and promote participation of men in fertility control programs.